Phenolic components and assessment of biological properties of Tchihatchewia isatidea Boiss. extracts: Docking and functional approaches for designing novel products - DOĞAN, AHMET (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The potentiality of bioactive phenolic compounds may result in plant extracts having multiple biological activities. The aim of this study was to investigate into the biological activities of the methanolic, ethyl acetate, and water extracts of Tchihatchewia isatidea Boiss, an endemic medicinal plant of Turkey. The phenolic compositions of the extracts were confirmed using RP-HPLC. Extracts were screened for their potential antioxidant through a panoply of assays; their anti-diabetic potential, and plausible inhibitory activity against tyrosinase and acetylcholinesterase. Molecular modelling methods were also used to assess the docking properties of phenolic compounds on tyrosinase. The major and most abundant compounds were rosmarinic acid (570 +/- 14 mu g/g extract in the methanolic extract), ferrulic acid (336 +/- 6 mu g/g extract in the methanolic extract), (+)-catechin (340 +/- 4 mu g/g extract in the water extract), apigenin (182 +/- 4 mu g/g extract in the methanolic extract), and epicatechin (188 12 g/g extract in the water extract). Radical scavenging, reducing capacity, and metal chelating activities were detected in the extracts, with preponderance activity observed in the methanolic extract. In conclusion, the potential clinical applications observed during this study may provide new insights into the molecular aspect particularly for neuroprotective and anti-diabetic mechanisms involving oxidative stress.
Keywords: Phenolics; Tchihatchewia isatidea; Anti-diabetic; Antioxidant; Tyrosinase inhibitor; Molecular docking; GREEN TEA CATECHINS; IN-VITRO; ANTIOXIDANT ACTIVITIES; PHYTOCHEMICAL PROFILE; INHIBITORY-ACTIVITIES; MEDICINAL-PLANTS; OXIDATIVE STRESS; MELANOMA-CELLS; FERULIC ACID; CHEMISTRY